2021
DOI: 10.1039/d1se00042j
|View full text |Cite
|
Sign up to set email alerts
|

Towards practical cells: combined use of titanium black as a cathode additive and sparingly solvating electrolyte for high-energy-density lithium–sulfur batteries

Abstract: The lithium–sulfur (Li–S) battery is considered one of the most promising technologies for next-generation energy storage. To realise its practical applications, electrodes with high areal sulfur loading, low-cost raw materials,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…Consequently, Cuisinier et al [100] , Lee et al [101] , Shyamsunder et al [102] proposed new different concepts of "sparingly solvating electrolytes", which consists of a low donor number solvent as a co-solvent or as a solo solvent when a low ion-pairing Li salt is used. Following this concept, other research groups, such as Nakanishi et al in Japan and Piwko et al in Germany, also actively contributed to this regard [103][104][105][106][107] . It is noteworthy that with the change from electrolytes with high PS solubility to such "sparingly solvating electrolytes", the whole cell chemistry is changed simultaneously.…”
Section: Qsspe Systemsmentioning
confidence: 98%
“…Consequently, Cuisinier et al [100] , Lee et al [101] , Shyamsunder et al [102] proposed new different concepts of "sparingly solvating electrolytes", which consists of a low donor number solvent as a co-solvent or as a solo solvent when a low ion-pairing Li salt is used. Following this concept, other research groups, such as Nakanishi et al in Japan and Piwko et al in Germany, also actively contributed to this regard [103][104][105][106][107] . It is noteworthy that with the change from electrolytes with high PS solubility to such "sparingly solvating electrolytes", the whole cell chemistry is changed simultaneously.…”
Section: Qsspe Systemsmentioning
confidence: 98%
“…In addition, the homogeneously distributed TiB contributes to the uniform growth of Li 2 S, thereby affecting the porosity of the discharged cathode. Our previous study [36] also demonstrated that sulfur cathodes show substantially different morphologies following the addition of TiB, especially after long‐term cycling. The porosity loss of the sulfur cathode was extremely severe in the case of TiB‐free cathodes, whereas it was maintained to a certain degree for the TiB‐added electrodes.…”
Section: Resultsmentioning
confidence: 85%
“…The poor wettability of the TiB‐free electrode to the electrolyte may also hinder the Li‐ion transport capability. In contrast, TiB included as a multifunctional sulfur cathode additive enabled the fabrication of crack‐free highly S‐loaded porous electrodes with a high wettability to the electrolyte [36] . To evaluate how these features affect the mass transport occurring within the sulfur cathode, we also examined the performance of the TiB‐added electrode under the same lean conditions using the G4 electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations